A Phase 2 Study of 16α-[(18)F]-fluoro-17β-estradiol Positron Emission Tomography (FES-PET) as a Marker of Hormone Sensitivity in Metastatic Breast Cancer (MBC) - Peterson, Lanell M. (2013)
PURPOSE: 16α-[(18)F]-fluoro-17β-estradiol positron emission tomography (FES-PET) quantifies estrogen receptor (ER) expression in tumors and may provide diagnostic benefit. PROCEDURES: Women with newly diagnosed metastatic breast cancer (MBC) from an ER-positive primary tumor were imaged before starting endocrine therapy. FES uptake was evaluated qualitatively and quantitatively, and associated with response and with ER expression. RESULTS: Nineteen patients underwent FES imaging. Fifteen had a biopsy of a metastasis and 15 were evaluable for response. Five patients had quantitatively low FES uptake, six had at least one site of qualitatively FES-negative disease. All patients with an ER-negative biopsy had both low uptake and at least one site of FES-negative disease. Of response-evaluable patients, 2/2 with low FES standard uptake value tumors had progressive disease within 6 months, as did 2/3 with qualitatively FES-negative tumors. CONCLUSIONS: Low/absent FES uptake correlates with lack of ER expression. FES-positron emission tomography can help identify patients with endocrine resistant disease and safely measures ER in MBC.